History of Plague Pathogen Plasmids Discovery - I. V. Darmov; S. N. Yanov; I. V. Marakulin (Вестник войск РХБ защиты)
To date, there is practically no available information about the leading role of Soviet military scientists in the discovery of extra-chromosomal heredity factors (plasmids) of Yersinia pestis the causative agent of the plague.The purpose of this work is to summarize all of the available materials about the plague pathogen plasmids discovery.The source base, method is the analysis of foreign and domestic unclassified materials on topic under consideration, including archival documents.Results and discussion. In 1972, US scientists, based on their experimental data, concluded that the plague pathogen (Yersinia pestis) had no extra-chromosomal DNA. Later, in 1975-1977, military scientists of the Research Institute of Microbiology of the Ministry of Defense of the USSR (RIM, now it is called Branch Office of the Federal State Budgetary Establishment “48 Central Scientific Research Institute” of the Ministry of Defence of the Russian Federation (Kirov)) have proven the existence of Yersinia pestis plasmids using sedimentation equilibrium ultracentrifugation, electron microscopy and agarose gel electrophoresis. It was established that the microbe has three own plasmids with molecular weights of 6.4, 47 and 67 megadalton (MDa). Soviet military microbiologists have revealed that the first plasmid encodes the synthesis of pesticine I, fibrinolysin and plasmocoagulase; the second one determines the calcium dependence and the synthesis of antigens V and W; and the third one determines the synthesis of antigen FI and mouse toxin. In 1978, T.G. Abdullin, E.V. Smirnov, I.V. Darmov (from RIM), as well as Academician I.V. Domaradsky (VNIIsintezbelok laboratory, Moscow) applied for a patent for the scientific discovery. The official USSR diploma for scientific discovery No. 001 under the code “Plasma” was issued in 1983, with the priority date of December 27th, 1977. The first unclassified publications confirming this discovery appeared only a few years later, in 1980–1981. Based on this discovery, new vaccine strains and protective antigens producer strains were designed, which made it possible to develop effective means of specific plague prevention.Conclusion. Available data and archival materials confirm the priority of Soviet military scientists in the plague pathogen plasmids discovery.